2014
DOI: 10.1186/1471-2156-15-52
|View full text |Cite
|
Sign up to set email alerts
|

Increased genetic diversity of ADME genes in African Americans compared with their putative ancestral source populations and implications for Pharmacogenomics

Abstract: BackgroundAfrican Americans have been treated as a representative population for African ancestry for many purposes, including pharmacogenomic studies. However, the contribution of European ancestry is expected to result in considerable differences in the genetic architecture of African American individuals compared with an African genome. In particular, the genetic admixture influences the genomic diversity of drug metabolism-related genes, and may cause high heterogeneity of drug responses in admixed populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
3
9
0
1
Order By: Relevance
“…In conclusion, our interrogation of CMA data from almost 100,000 individuals identified low frequency pharmacogenomic CNVs at the clinically relevant CYP2C region in the general population. These results are consistent with previously reported pharmacogenomic sequencing studies, which identified a spectrum of rare pharmacogenomic variants that are likely to be functional (Bush et al, ; Gordon et al, ; Li et al, ; Nelson et al, ). Although the identified CYP2C deletion and duplication alleles have low frequencies in the studied populations, their contribution to an individual's CYP2C19 and CYP2C9 metabolizer phenotype status is most likely clinically relevant.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In conclusion, our interrogation of CMA data from almost 100,000 individuals identified low frequency pharmacogenomic CNVs at the clinically relevant CYP2C region in the general population. These results are consistent with previously reported pharmacogenomic sequencing studies, which identified a spectrum of rare pharmacogenomic variants that are likely to be functional (Bush et al, ; Gordon et al, ; Li et al, ; Nelson et al, ). Although the identified CYP2C deletion and duplication alleles have low frequencies in the studied populations, their contribution to an individual's CYP2C19 and CYP2C9 metabolizer phenotype status is most likely clinically relevant.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, our interrogation of CMA data from almost 100,000 individuals identified low frequency pharmacogenomic CNVs at the clinically relevant CYP2C region in the general population. These results are consistent with previously reported pharmacogenomic sequencing studies, which identified a spectrum of rare pharmacogenomic variants that are likely to be functional (Bush et al, 2016;Gordon et al, 2014;Li et al, 2014;Nelson et al, 2012…”
Section: Interestingly Cyp2c19 Deletions Have Previously Been Reportsupporting
confidence: 93%
See 2 more Smart Citations
“…ADME-related genetic variability often differs across populations [94] and helps to explain the link between ancestry and variable chemotherapy drug response [95]. Li et al observed greater diversity in ADME genes for the African-American population compared with European and African populations [96], predisposing African-Americans to more variable drug response. Gene variations may alter drug metabolism by activating or inactivating a medication, activating or inactivating a drug's metabolite, affecting the medication's transport, or affecting the drug's intended target [97].…”
Section: Genomics and Epigenomics Of Symptoms And Chemotherapy Metabomentioning
confidence: 99%